PARADIGMA PENDIDIKAN ANAK DALAM PERSPEKTIF SITI HAJAR - Siti Zulfa Alawiyah (Nurul Jadid University, 2019)
The research is motivated by concern about existing children’s education. Where parents, especially mother’s, are confused and difficult to find figures in educating their children. All parents, especially Muslim mothers expect their children to be pious, obedient to worship to Allah SWT, devoted to his parents. Model to educate children is from the wife of the prophet Ibrahim A. S., Siti Hajar who has succesfully educated his son Ismail so that he becomes a pious child, obediently worshiping Allah SWT and serving his parents. This research uses a historical analysis approach, by studying and exploring the historical facts about Siti Hajar in educating his son Ismail as well as the present conditions and be analyzed which will give birth to a complete understanding of he stages carried in educating children.